SER performance optimisation of AF cooperative communication system based on directional antenna. (2018) - Tan, Ruilian; Li, Zhe; Su, Xi
Aiming at the cooperative communication system with directional antenna, this paper has studied the SER (Symbol Error Rate) performance under AF (Amplify-and-Forward protocol). The model of AF cooperative communication system using directional antenna was firstly established to deduce the closed-form expression of SER in this model as well as the upper limit of SER. Then, the OPA (Optimum Power Allocation) was also analysed on the purpose of minimising SER. Combining specific simulation numerical values, SER performance of established model was thoroughly researched in this paper. Simulation results demonstrate that system SER obviously decreases by adopting cooperative communication system with directional transmitting and directional receiving. Each node's directional gain, channel quality and power allocation method all have great influence on system's overall performance. And the OPA is also proved to be superior to EPA (Equal Power Allocation).